2021
DOI: 10.3390/toxins13110742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Lateral Flow Devices for Total Aflatoxins with Special Emphasis on Their Robustness under Sub-Saharan Conditions

Abstract: As aflatoxins are a global risk for humans and animals, testing methods for rapid on-site screening are increasingly needed alongside the standard analytical laboratory tools. In the presented study, lateral flow devices (LFDs) for rapid total aflatoxin screening were thoroughly investigated with respect to their matrix effects, cross-reactivity, their performance under harsh conditions in Sub-Saharan Africa (SSA), and their stability, as well as when compared with liquid chromatography-tandem mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the study, the RIDA smart phone application correlation coefficient was average in aflatoxin analysis. In Cvak et al (2021), it is described that during analysis when the maize flour is not well refined during grinding, spot and cross contamination while handling maize samples, analysing samples with temperature of above 30 o centigrade, when using lateral flow disks results are affected. The validation of Reveal Q+ MAX for aflatoxin testing with Accuscan gold reader was done by Le et al (2019) who confirmed that the machine was adequate in detection and quantification of mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the RIDA smart phone application correlation coefficient was average in aflatoxin analysis. In Cvak et al (2021), it is described that during analysis when the maize flour is not well refined during grinding, spot and cross contamination while handling maize samples, analysing samples with temperature of above 30 o centigrade, when using lateral flow disks results are affected. The validation of Reveal Q+ MAX for aflatoxin testing with Accuscan gold reader was done by Le et al (2019) who confirmed that the machine was adequate in detection and quantification of mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…However, short-term (up to 16 h) storage before testing with the Panbio COVID-19 Ag Rapid Test Device (Abbott) at extreme temperatures (freezing at −4.0 to 113.0°F [−20.0 to 45.0°C]) did not impact sensitivity or specificity ( 7 ). Cvak et al ( 8 ) have also reported that an aflatoxin LFT maintained performance in Sub-Saharan conditions (≤101.1°F [≤38.4°C], ≤91% relative humidity) at 3 cutoffs throughout a 5-month study period. Focusing on device design, Kaur et al 2021 ( 9 ) evaluated the effects of long-term storage on the nitrocellulose membranes used in LFTs, finding that lateral rates of membranes in sealed packaging were significantly reduced at temperatures of 99°F (37°C) and 113°F (45°C) after 2 months of storage, which concurs with the reduced sensitivity described above.…”
Section: Observationmentioning
confidence: 91%
“…While the main innovations deal with the detection platforms, sample extraction procedures are still 'traditional' and no steps forward in aqueous-based 'green' protocols have been reported so far. Cvak et al (2021) reported on a comprehensive study to evaluate the fitness for purpose of commercially available qualitative LFIA (cut off levels of 4 µg/kg, 10 µg/kg, and 20 µg/kg defined by the LFIA manufacturer) for on-site analysis of aflatoxins under Sub-Saharan conditions. First, matrix effects were evaluated by screening different nut samples: no false negative results were obtained, and overall the matrix type had a slight influence on the cut off values of the tests.…”
Section: Single Mycotoxin or Single Mycotoxin Family Biosensorsmentioning
confidence: 99%